Dopant engineering for ZnO electron transport layer towards efficient perovskite solar cells - Zainal Abidin, Nurul Aliyah; Arith, Faiz; Noorasid, Nur Syamimi; Sarkawi, Hafez; Muhammad Mustafa, Ahmad Nizamuddin; Safie, Nur Ezyanie; Mohd Shah, Ahmad Syahiman; Mohd Abid, Mohd Asyadi 'Azam; Chelvanathan, Puvaneswaran; Amin, Nowshad (Royal Society of Chemistry, 2023)
The conventional electron transport layer (ETL) TiO2 has been widely used in perovskite solar cells (PSCs), which have produced exceptional power conversion efficiencies (PCE), allowing the technology to be highly regarded and propitious. Nevertheless, the recent high demand for energy harvesters in wearable electronics, aerospace, and building integration has led to the need for flexible solar cells. However, the conventional TiO2 ETL layer is less preferred, where a crystallization process at a temperature as high as 450 °C is required, which degrades the plastic substrate. Zinc oxide nanorods (ZnO NRs) as a simple and low-cost fabrication material may fulfil the need as an ETL, but they still suffer from low PCE due to atomic defect vacancy. To delve into the issue, several dopants have been reviewed as an additive to passivate or substitute the Zn2+ vacancies, thus enhancing the charge transport mechanism. This work thereby unravels and provides a clear insight into dopant engineering in ZnO NRs ETL for PSC.